Hormonal contraceptive use before and after conception in relation to preterm birth and small for gestational age: an observational cohort study. (16th October 2014) - Jensen, ET; Daniels, JL; Stürmer, T; Robinson, WR; Williams, CJ; Vejrup, K; Magnus, P; Longnecker, MP
<x xml:space="preserve">Abstract</x> Objective To evaluate whether hormonal contraceptives, used before or in early pregnancy, confer increased risk of preterm birth or reduced fetal growth. Design Population‐based cohort study conducted by the Norwegian Institute of Public Health (Mother and Child Cohort Study, 1998–2008) with linkage to the Norwegian Prescription Registry and to the Medical Birth Registry of Norway. Setting Norway. Population Of the 48 615 pregnancies meeting study inclusion criteria, 44 734 pregnancies were included in the complete case analysis. Methods We characterised hormonal contraception by type (combination oral, progestin‐only oral, vaginal ring, transdermal, and injectable) and specific progestin component. We used generalised estimating equations to estimate the odds of adverse outcome according to formulation used. Several sensitivity analyses were conducted. Main outcome measures Preterm birth, small for gestational age. Results We observed a positive association between use of a combination oral contraceptive and preterm birth for all exposure periods (e.g. adjusted odds ratio 1.21, 95% confidence interval 1.04–1.41 for last use 12 to >4 months before conception); combination contraceptives containing the progestin norethisterone were consistently related to risk. Other types of hormonal contraception were generally not associated with preterm birth; none were related to small for gestational age. Observed associations were robust to sensitivity analyses. Conclusion Hormonally active agents may exert dose‐, agent‐, and timing‐specific effects on growth and development. We found that the particular progestin component is important when assessing the potential for adverse effects among former users of hormonal contraceptives.